LAJU PERTUMBUHAN, EFISIENSI PEMANFAATAN PAKAN, KANDUNGAN POTASIUM TUBUH, DAN GRADIEN OSMOTIK POSTLARVA VANAME (Litopenaeus Vannamei, Boone) PADA POTASIUM MEDIA BERBEDA - Kaligis, Erly Y (Sam Ratulangi University, 2010)
Effect of K+ concentration on growth rate, feed efficiency, potassium whole body, and osmoregulatory capacity of L. vannamei postlarvae Boone, 1931 were investigated. Treatments consisted of different concentration of K+ added to distilled water. Four treatments were set, namely A, B, C and D, where K2CO3 levels were 0, 30, 60 and 90 ppm, respectively. After the 42-days feeding trial, growth rate and potassium whole body of the shrimp under treatment D (90 ppm K2CO3) were significantly higher, while the value of osmoregulatory capacity in treatment A (0 ppm K2CO3) significantly higher than those under the other four treatments. The results indicated treatment C (60 ppm K2CO3) were the optimum K+ level for growth rate with increasing body size.